PENGARUH AI COMPETENCY TERHADAP SUSTAINABLE AND RESPONSIBLE PEDAGOGICAL AI USE (SRPAI): PERAN MODERASI ETHICAL AWARENESS PADA GURU SMK NEGERI 2 SALATIGA - Barbalina Rommer; Krismiyati Krismiyati (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
This study aims to analyze the effect of AI Competency on Sustainable and Responsible Pedagogical AI Use (SRPAI) and to examine the role of Ethical Awareness as a moderating variable among Computer Network Engineering (TKJ) teachers at SMK Negeri 2 Salatiga. This issue is important because the successful use of AI in vocational learning depends not only on technological mastery but also on users' ethical considerations. The study employed a mixed-method, cross-sectional survey design, combining quantitative data from teachers at SMK Negeri 2 Salatiga analyzed using PLS-SEM and Split Analysis Moderation, with qualitative data from interviews with six TKJ teachers analyzed through thematic coding. The findings show that AI Competency meaningfully drives teachers toward applying AI appropriately and responsibly in learning. However, ethical awareness functions as a filtering mechanism: teachers with higher ethical understanding tend to be more selective and cautious in using AI, making the link between competency and AI use even stronger among teachers with lower ethical awareness. Interview findings reinforce this pattern, showing that teachers with higher ethical awareness are more likely to re-check AI outputs before use and consider their impact on students. This study confirms that developing teachers' AI competency must be accompanied by strengthening ethical capacity so that AI use in vocational education proceeds responsibly rather than merely quickly and intensively. ABSTRAK Penelitian ini bertujuan menganalisis pengaruh AI Competency terhadap Sustainable and Responsible Pedagogical AI Use (SRPAI) serta menguji peran Ethical Awareness sebagai variabel moderator pada guru Teknik Komputer dan Jaringan (TKJ) SMK Negeri 2 Salatiga. Isu ini penting dikaji karena keberhasilan pemanfaatan AI dalam pembelajaran vokasi tidak hanya bergantung pada penguasaan teknologi, tetapi juga pada pertimbangan etika penggunanya. Penelitian menggunakan desain mixed-method cross-sectional survey, memadukan data kuantitatif dari guru SMK Negeri 2 Salatiga yang dianalisis menggunakan PLS-SEM dan Split Analysis Moderation, dengan data kualitatif dari wawancara enam guru TKJ yang dianalisis melalui thematic coding. Hasil penelitian menunjukkan bahwa AI Competency berkontribusi nyata mendorong guru menerapkan AI secara tepat dan bertanggung jawab dalam pembelajaran. Namun, kesadaran etis justru berperan sebagai penyaring yang membuat guru dengan pemahaman etika tinggi bersikap lebih selektif dan berhati-hati dalam memanfaatkan AI, sehingga hubungan antara kompetensi dan penggunaan AI justru lebih kuat pada guru dengan kesadaran etis rendah. Temuan wawancara memperkuat pola tersebut, memperlihatkan bahwa guru dengan kesadaran etis tinggi cenderung memeriksa kembali keluaran AI sebelum digunakan dan mempertimbangkan dampaknya bagi peserta didik. Penelitian ini menegaskan bahwa pengembangan kompetensi AI guru perlu disertai penguatan etika agar pemanfaatan AI dalam pendidikan vokasi berlangsung bertanggung jawab, bukan sekadar cepat dan intensif.